The Effect of a Maze Game on The Vocabulary Mastery of Ninth Grade Students at SMPN 1 Tegalsari in The Academic Year 2025/2026 - Silvana Faslah Qori; Scheva Fitrah Pratama Haris; Nafa Brian Janata; Serli Eka Bintang Lestari; Yuli Sugianto (MAN Insan Cendekia Jambi, 2025)
Vocabulary is a crucial component in language proficiency that supports students' communication skills. This study was conducted to know the effect of a maze game on the Vocabulary Mastery of Ninth Grade Student at SMPN 1 Tegalsari in the Academic Year 2025/2026. This study used a quasi-experimental design with a one-group pretest-posttest approach. The participants of this study consisted of 33 of ninth C grade students. Data was collected using a vocabulary test consisting of 30 multiple-choice questions items that focused on synonym and antonym in three categories: verbs, nouns, and adjectives. With SPSS version 27, the statistical analysis was carried out. The results showed a significant increase in vocabulary scores, where the mean score of the pre-test was 51 and increased to 79 in the post-test. The paired sample t-test showed a t-value of 23.767, higher than the t-table value of 2.036 with a significance level below 0.05, indicating a statistically significant difference. This study shows that the use of maze game can help students increase their vocabulary mastery. In this study, focusing on word recognition in the categories of verbs, nouns, and adjectives was proven to facilitate students' vocabulary mastery. Therefore, Maze Game has effect on students' vocabulary mastery, especially their understanding in adjectives.